Korelasi Keterampilan Metakognitif Terhadap Kemampuan Siswa Dalam Memecahkan Masalah dengan menggunakan Model Pembelajaran Project Based Learning (PjBL) - Emayulia Sastria; Heva Afrillia; Dinyah Rizki Yanti Zebua; Dharma Ferry (Jurnal Biotek, 2023)
Copyright©2023 Metacognitive urgency is required to develop students' problem-solving abilities because learning requires students to develop not only cognitive abilities but also high reasoning skills. This study aimed to determine the relationship between metacognitive skills and students' ability to solve problems in biology using the PjBL model. This study was quantitative research with a correlational approach. The research was conducted over the course of a month in August 2022. The data analysis technique used was the Normality Test using the Kolmogorov-Smirnov Z-test, followed by the Pearson Correlation Test to determine the existence and magnitude of the relationship between variable X and variable Y, others expressed in percent. The metacognitive skills of students at SMAN 4 Sungai Penuh fall into the high category, with a percentage of 76.11%. However, the ability of students to solve problems in Biology subjects using the PjBL model at SMAN 4 Sungai Penuh is categorized as low, with a percentage of 52.23%. The study found no correlation between students' metacognitive skills and their ability to solve problems in the Biology subject using the PjBL model at SMAN 4 Sungai Penuh. Furthermore, there was no correlation observed between the indicators of students' metacognitive skills and their problem-solving abilities in Biology using the PjBL model in SMAN 4 Sungai Penuh.